Binding Se into nitrogen‐doped porous carbon nanosheets for high‐performance potassium storage. Issue 4 (25th February 2021) - Huang, Huijuan; Luo, Xiao; Yao, Yu; Zhou, Xuefeng; Jiang, Yu; Guo, Chunli; Liu, Jiaqin; Wu, Xiaojun; Yu, Yan
Abstract: Selenium cathode has been demonstrated as a promising candidate of cathode material for low‐cost and high‐energy density potassium ion batteries (PIBs). Nevertheless, their applications are prevented by poor electrochemical performance due to the shuttle effect of high‐order polyselenides, the sluggish diffusion of bigger K +, and the huge volumetric expansion during cycling. In this work, we design a multifunctional Se host (N‐HCNS) by grafting ZIF‐8‐derived microporous carbon onto the surface of N‐doped porous carbon nanosheets. The obtained N‐HCNS carbon matrix integrates conductivity, captivity, and immobility abilities, which inhibits the polyselenides shuttle, improves the Se utilization, and buffers the volume change during cycling. The 3D hollow carbon skeleton enhances the infiltration of electrolytes. As an cathode for PIBs, the Se@N‐HCNS electrode delivers an unprecedented life‐span (260 mAh g −1 at 1.0 A g −1 after 2000 cycles) and exhibits a remarkable rate capacity (339 mAh g −1 at 5.0 A g −1 ). Density functional theory (DFT) calculation reveals the effective adsorption of K2 Se with pyridine and pyrrole nitrogen doping in carbon matrix. The unique synergetic design of electrode not only gives insight into the reaction mechanism but also highly emphasizes the potential capabilities of N‐doped carbon in K‐Se batteries. Abstract : The nitrogen‐doped porous carbon nanosheets as the multifunctional host of Se (Se@H‐HCNS) are successfully synthesized, which realizes high‐energy density and ultra‐long cycle life for K‐Se battery. The excellent electrochemical performance can be attributed to the chemical bonding between Se and carbon matrix, hierarchical pore architecture, and high content of nitrogen doping in.